Relationship between pulmonary exacerbations and daily physical activity in adults with cystic fibrosis. Issue 1 (December 2015) - Savi, Daniela; Simmonds, Nicholas; Di Paolo, Marcello; Quattrucci, Serena; Palange, Paolo; Banya, Winston; Hopkinson, Nicholas; Bilton, Diana
Abstract Background The aim of this study was to examine the relationship between pulmonary exacerbations and physical activity (PA) in adults with cystic fibrosis (CF). Methods We grouped adults with CF according to their exacerbation status in the year before study enrolment: (1) <1 exacerbation/year; (2) 1–2 exacerbations/year; and (3) >2 exacerbations/year. PA was assessed objectively by means of an accelerometer at the time of study enrolment. Results Patients with >2 exacerbations/year spent less time in PA; specifically, fewer activities of mild intensity [>3 metabolic equivalents (METs)], and lower active energy expenditure (P  = 0.01 andP  = 0.03, respectively). After correcting for relevant confounders, PA levels were not related to the exacerbation frequency in the preceding year. PA at moderate intensity (4.8–7.2 METs) or greater (>7.2 METs) was independently associated with gender and FEV1 % predicted (P  = 0.007 andP  = 0.04, respectively). Compared with men, women had reduced vigorous activities (P  = 0.01) and active energy expenditure (P  = 0.01). Conclusions Adult CF patients with more pulmonary exacerbations in the preceding year have more advanced disease and are less active than their peers. PA was independently associated with gender and airflow obstruction. Gender differences in PA are evident in CF adults.